2022
DOI: 10.3389/fonc.2022.1036401
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 promotes osteosarcoma progression through activating CDK4/RB/E2F1 signaling pathway

Abstract: Osteosarcoma (OS) is a primary malignant tumor of the bone characterized by poor prognosis due to chemotherapy resistance and high recurrence rates. DJ-1 (PARK7) is known as an oncogene and its abnormal expression is related to the poor prognosis of various types of malignant tumors. It was found in this study that upregulated expression of DJ-1 was closely correlated with the prognosis of OS patients by promoting the proliferation, migration and chemotherapy resistance of OS cells in vitro through regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is also targeted by tiny DNA tumor virus-transforming proteins [30,31] . Han et al revealed that DJ-1 promotes osteosarcoma progression by activating the CDK4/RB/E2F1 signaling pathway [32] . Liu et al found that long noncoding RNA (lncRNA)-TMPO-AS1 promotes osteosarcoma cell apoptosis by targeting and regulating E2F1 [33] .…”
Section: Discussionmentioning
confidence: 99%
“…It is also targeted by tiny DNA tumor virus-transforming proteins [30,31] . Han et al revealed that DJ-1 promotes osteosarcoma progression by activating the CDK4/RB/E2F1 signaling pathway [32] . Liu et al found that long noncoding RNA (lncRNA)-TMPO-AS1 promotes osteosarcoma cell apoptosis by targeting and regulating E2F1 [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence shows that DJ-1 may be involved in various mechanisms in cancer progression, including the inhibition of cellular apoptosis, redox sensing, acting as a marker for chemotherapy resistance, suppression of ferroptosis, regulating histone glycation, and inhibition of autophagy [9][10][11][12][13]. It has been identified overexpression in a range of cancer types, including breast cancer [14,15], osteosarcoma [16], melanoma [17], colorectal cancer [18], endometrial cancer [19], and esophageal cancer [20], indicating its role as oncogene. Previously, a study in breast cancer cell lines has shown that NRG-I promotes the decoupling of DJ-I with HER3 and activates the heterodimerization of HER2/HER3 [21].…”
Section: Introductionmentioning
confidence: 99%